Violencia económica y sus consecuencias en el bienestar integral de las mujeres del barrio Esperanza del cantón Olmedo, en la actualidad - Vargas Ordoñez, Jhoana Del Cisne (2025)
Economic violence is a problem that generates enormous damage to those who suffer it, which is why it has become a worldwide concern because it is a type of violence that is invisible and has not been taken into account, such is the case of the Ecuadorian state, since it has not developed laws or public policies that respond to it. For this reason, the objectives of the study were aimed at: analyzing the consequences of economic violence on the integral wellbeing of women in the Esperanza neighborhood of the Olmedo canton, using a mixed methodology of exploratory type, a transversal - non-experimental design, in addition, the research was carried out with 30 women. Also, a bibliographic file was applied to gather information about the phenomenon of study, in second instance, a questionnaire was used in order to know the causes and effects that economic violence generates. Also, the design of an intervention proposal was developed in which the findings obtained allowed the realization of an intervention plan focused on providing the necessary tools to raise awareness, sensitize and empower women victims of economic violence to prevent this social phenomenon. In this way, the research highlights that the results showed that economic violence is a problem capable of causing damage to physical, emotional, social and professional well-being, which is why it is vital to develop mechanisms to address this identified phenomenon